KECERIA (Kegiatan Cerdaskan Remaja Putri dari Anemia): Menciptakan Sekolah Bebas Anemia - Hubaybah, Hubaybah; Azhary, Muhammad Rifqi; Simatupang, Nanda Agustian; Herwansyah, Herwansyah; Amir, Andy; Ningsih, Vinna Rahayu (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Anemia in adolescent girls can have long-term impacts on themselves and their future children. Low knowledge of adolescents about anemia is the biggest factor causing anemia, especially school children who have unhealthy snack habits and unhealthy diets. The KECERIA program aims to educate adolescent girls. This activity was carried out at SMK Negeri 4, Jambi City, targeting adolescent girls. This activity was carried out in May-July 2024 with stages, advocacy, socialization, and nutrition education for 34 adolescent girls. Quantitative assessments were carried out pre- and post-tests before and after nutrition education. The average knowledge score before being given education was 59.41 and increased to 80.88 during the post-test. The results of the Paired Samples Test statistical analysis (Dependent T Test) found a P value = <0.0001, which means that there is a difference in the average knowledge of respondents in the pre-test and post-test results of SMK Negeri 4, Jambi City students after being given education. Providing education about anemia has an influence on the level of knowledge of female adolescents at SMK Negeri 4, Jambi City. It is recommended that schools routinely provide education about preventing anemia for female students in order to increase the knowledge, attitudes and behavior of female students in preventing anemia.